Application of a number of physical and chemical analysis methods the assessment of a multicomponent sample composition of natural water - L. V. Trubacheva; S. Yu. Lohaninа; T. I. Belova (Стандартные образцы)
The authors present experimental data on the development of a special sample in the form of a dispersed material that simulates the mineral macro-component composition of natural surface water. The results of the study obtained by a number of physico-chemical analysis methods were compared to determine the mass concentration of the micro-component - manganese (II) in the sample. Determination of the mass concentration of manganese (II) was carried out by the methods of spectrophotometry for PND F 14.1:2.61, x-ray fluorometry for PND F 14.1:2:4.130, inversion voltammetry for PND F 14.1:24.217.Procedures for establishing the metrological characteristics of a special sample to control the accuracy of the results of measurements of the mass concentration of manganese (II) using a number of physicо-chemical analysis methods have been carried out.A number of advantages and disadvantages of certified measurement methods that are widely used in chemical laboratories for determining the content of manganese in natural surface water are noted. The necessity of carrying out the procedure of certification of the spectrophotometric method with the use of manganese (II) ions - sodium periodate as an oxidizer is shown.